Case study on team teaching Pluridisciplinary courses : 2020 a framework for course development. - West, Jason M.; Southam, Collette; Hrivnak, George (Australia. Dept of Education, Skills and Employment, 2020)
This case study assesses pluridisciplinary course delivery through the use of the framework developed through our research. Team-teaching methods, as a natural extension of learning and teaching in pluridisciplinary fields, are examined. In particular, the framework is applied to business school courses where team teaching is already undertaken. This study was designed to consult, share, and create awareness of alternative learning and teaching practices for pluridisciplinary fields. Pluridisciplinarity, coined by Max-Neef (2005), requires two or more disciplines to combine their expertise to jointly develop and deliver learning and teaching outcomes appropriate for a subject area, especially one that is rapidly changing. Emerging careers in business coupled with necessary graduate outcomes mandate the need for a truly pluridisciplinary pedagogical approach. Pluridisciplinary collaboration occurs when people from different professions or disciplines with varied skills and experiences complement each other when working toward achieving a common objective. [Publisher summary, ed]